RESEARCH ON FLEXIBLE IMPACT OF CRANK AND CONNECTING ROD MECHANISM OF AUTOMATIC GUN (MT) - DOU Zheng; LI Yong; CHEN YongGang (Jixie qiangdu)
For the centroid of crank connecting rod of automatic gun is moving continuously in longitudinal direction, under the condition of alternating high and low overload, the crank and connecting rod are subjected to the alternating time-varying inertia load, resulting in dynamic deflection and flexible impact of automatic gun; The causes and characteristics of flexible impact are analyzed. According to the definition of inertia load in D’Alembert principle, the inertial load is introduced as boundary condition in finite element analysis; Under the condition of the action of gunpowder gas with time varying law of Sergey Mamontov, the movement simulation analysis of crank connecting rod mechanism is carried out, and the law of crank and connecting rod overload and saltus is obtained; The dynamic deflection（deformation quantity） of crank connecting rod under inertia load is analyzed by finite element method. The results show that the connecting rod becomes the main source of vibration when the overload is more than 25 000 m/s~2. The dynamic deflection can be reduced by reducing the center distance of the rotating pair and the mass distribution near the centroid, thus reducing the dynamic deflection and reducing the flexible impact.